The “Debate” about Poland - Jessica Sofizade (Ksiegarnia Akademicka Publishing, 2019)
This paper examines two speeches made by Janusz Lewandowski and Ryszard Antoni Legutko in the European Parliamentary debate entitled “The situationof the rule of law and democracy in Poland” on 15/11/2017.  In particular, it analyses their representations of Poland and the EU, and aims to determine whether they can be considered as “populist” according to J.-W. Müller’s criteria of populism. It is suggested that Legutko’s speech can be labelled populist according to Müller’s criteria, whilst Lewandowski does not face this charge to the same extent, even though his speech uses similar linguistic methods.